The Contribution of Cooperative Energy Communities to Combating Energy Poverty - Meira, Deolinda; Mota, Marta; Cunha, Ricardo (Cooperativismo & Desarrollo, 2025)
This article examines the potential of energy communities established in cooperative form as an instrument to combat energy poverty. The literature review conducted shows that, although Portuguese legislation does not impose a specific legal form for these communities, the cooperative model proves particularly suitable for addressing this social problem. This results from the convergence between the legal framework of energy communities — whether renewable energy communities or citizen energy communities — and the cooperative principles, which are based on voluntary membership, democratic control, and the pursuit of collective interest. This study demonstrates that, by prioritizing environmental, economic, and social benefits over financial profit, cooperatives offer a governance and value-sharing model capable of reducing inequalities in access to energy, fostering greater energy justice and contributing, sustainably, to the mitigation of energy poverty.Keywords: Energy communities; Cooperatives; Legislation; Energy poverty.
Keywords: Energy communities; Cooperatives; Legislation; Energy poverty